JAPANESE HIGHER EDUCATION SYSTEM AND PEDAGOGICAL TECHNOLOGY USED IN IT. - Khushvakhtov Jakhongir Nurullo ugli; Aripov Khodjiakmal Khodjiakbarovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Japan's higher education system is a very powerful tool for their national politics and culture. Academic achievements of students studying in Japan are high and in line with international criteria and standards. General policy, management and administration are under the Ministry of Education.